Plurarisme Sanksi Pidana antara Blue Collar Crime dan White Collar Crime dalam Prespektif Keadilan - Pranata, Elda; Yustia, Dewi Asri (Universitas Batanghari Jambi, 2025)
This study examines the pluralism of criminal sanctions between blue-collar crime and white-collar crime from a justice perspective, focusing on the disparities in law enforcement in Indonesia. Blue-collar crimes, typically committed by individuals from lower socioeconomic classes, such as theft or violence, often receive harsh penalties like imprisonment. In contrast, white-collar crimes, perpetrated by individuals of higher socioeconomic status, such as corruption or embezzlement, tend to receive lighter sanctions, such as fines or probation. This disparity raises questions about substantive justice and the principle of equality before the law. Employing a normative juridical approach, this study analyzes relevant legislation, including the 1945 Constitution, the Criminal Code, and Law No. 39 of 1999 on Human Rights, alongside case studies such as the Nenek Asyani case, the Bank Century scandal, and the HM tin corruption case. The findings reveal that law enforcement for blue-collar crimes is often swift and retributive, while white-collar crimes are frequently hindered by power dynamics, political connections, and legal impunity, undermining deterrence and social justice. Grounded in Pancasila’s justice theory and punishment theories (absolute, relative, and combined), this study highlights the need for balanced sentencing reforms, prioritizing restorative justice for blue-collar crimes and proportional sanctions for white-collar crimes. It recommends strengthening the independence of law enforcement, implementing mediation for minor cases, and adjusting criminal policies to ensure fair punishment proportional to the crime’s impact. Thus, this study contributes to the discourse on inclusive and responsive criminal justice in addressing social dynamics.